Lived experience of neuropsychiatric symptoms among females with mild cognitive impairment: A phenomenological study. (29th October 2021) - Lin, Rose S. Y.; Yu, Doris S. F.; Li, Polly W. C.; Chau, Pui Hing; Lee, Jung Jae
Abstract: Aims: To explore the lived experience of neuropsychiatric symptoms (NPS) among females with mild cognitive impairment (MCI). Design: A phenomenological study using individual, semi‐structured, telephone‐based interviews was conducted to explore how the NPS are aroused, evolve, and affect the overall well‐being, illness perception and the corresponding coping responses adopted by females with MCI. Methods: Twenty‐nine participants with MCI were recruited from the community setting in Hong Kong between March and October 2020. Interviews were audio‐recorded, transcribed verbatim, and analysed using an interpretative phenomenological analysis approach and constant comparison strategy. Results: Three themes were identified: (1) living vigilant lives with threats and uncertainty, (2) snowballing into further negative emotions and (3) seeking outlets for negative emotions. Our findings suggested that the participants' cognitive, functional and social challenges aroused intense emotional responses such as depression, agitation and anxiety. These noting negative emotions were further perpetuated by maladaptive coping responses, unrealistic expectations from coping strategies and overwhelming disease burden. Various internal and external strategies were adopted to enhance emotional adaptation, of which adopting a positive attitude appeared to be the most promising strategy. Conclusion: This study shed light on the challenging experience of MCI. The cognitive afflictions and the resultant impacts on various life domains evoked a cluster of NPS. Support services need to enhance emotional adjustment through alleviating the various life stressors and strengthening the coping resources. Impact: Elucidating the lived experience of NPS provides important insights into the development of a more effective, comprehensive and person‐centred care planning for the population with MCI. Holistic care planning should extend beyond cognitive health optimization into enhancing disease knowledge, improve emotional coping, rebuild self‐identity and bolstering social supports among this preclinical cohort.